Corporate Social Responsibility in Europe : united in sustainable diversity - Idowu, Samuel O.; Fifka, Mathias S.; Schmidpeter, René (Libros electrónicos en Ebscohost, 2015)
This book explores the current state of Corporate Social Responsibility (CSR) in 24 European nations, examining the state of the development and practice of CSR and sustainability for organizations in these countries. The common denominator for all of the book?s 25 chapters is a management perspective rather than an ethical discourse. The book therefore represents a comprehensive survey of initiatives and activities in the field of CSR and provides a wealth of complete cases and examples for different approaches to sustainable and responsible management practice. The book also reviews the relevant political and governmental guidelines and frameworks for organizations, both on a national and a European level. Europe has taken a leading role in the promotion and implementation of CSR. This book showcases how, through CSR, enterprises can significantly contribute to achieving the European Union?s treaty objectives of sustainable development and a highly competitive social market economy.